Rovalpituzumab Tesirine: A Novel DLL3-Targeting Antibody-Drug Conjugate - Bilal H. Lashari; Yazhini Vallatharasu; Lakshmi Kolandra; Mohsin Hamid; Dipesh Uprety (Adis, Springer Healthcare, 2018)
Abstract Small cell lung cancer (SCLC) comprises about 15% of all cases of lung cancer. In recent years, owing to a change in the epidemiology of smoking habits, the incidence of the tumor has decreased; however, it remains a significant challenge to global health. While the tumor has a favorable initial response to chemoradiation, relapse is invariable, and second-line regimens may be intolerable given the severity of side effects. For patients with tumors resistant to second-line regimens, no current standard regimens exist. Rovalpituzumab tesirine is a novel antibody-drug conjugate, targeting delta-like protein 3, fundamental in the downstream cellular signaling for proliferation and apoptosis. This drug is reported to have shown promise in pre-clinical and phase I trials. It appears effective in decreasing tumor burden and is reported to be well tolerated, albeit with a significant adverse effect profile. Currently, it is being studied as part of initial and subsequent line chemotherapeutic regimens; it remains to be seen if this is a viable option in the treatment of SCLC. This may add to the agents that can be used against SCLC, and help improve outcomes.